The Light-Induced WD40-Repeat Transcription Factor DcTTG1 Regulates Anthocyanin Biosynthesis in Dendrobium candidum - Jia, Ning; Wang, Jingjing; Wang, Yajuan; Ye, Wei; Liu, Jiameng; Jiang, Jinlan; Sun, Jing; Yan, Peipei; Wang, Peiyu; Wang, Fengzhong; Fan, Bei (Frontiers in Plant Science, 2021)
Dendrobium candidum is used as a traditional Chinese medicine and as a raw material for functional foods that possess anti-oxidative, anti-angiogenic, and immunostimulatory properties. D. candidum stems are green or red, and red stems are richer in anthocyanins. Light is an important environmental factor that induces anthocyanin accumulation in D. candidum. However, there is no detailed information on the underlying molecular mechanisms. In this study, we exposed D. candidum seedlings to two different light intensities and found that strong light increased the anthocyanin content and the expression of genes involved in anthocyanin biosynthesis. Through transcriptome profiling and expression analysis, we identified a WD40-repeat transcription factor, DcTTG1, whose expression is induced by light. Yeast one-hybrid assays showed that DcTTG1 binds to the promoters of DcCHS2, DcCHI, DcF3H, and DcF3'H, and a transient GUS activity assay indicated that DcTTG1 can induce their expression. In addition, DcTTG1 complemented the anthocyanin deficiency phenotype of the Arabidopsis thaliana ttg1-13 mutant. Collectively, our results suggest that light promotes anthocyanin accumulation in D. candidum seedlings via the upregulation of DcTTG1, which induces anthocyanin synthesis-related gene expression.